2020
DOI: 10.1177/2329488420907148
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Variations in Corporations’ Communication After a CA Versus CSR Crisis: A Semantic Network Analysis of Sustainability Reports

Abstract: The study attempts to understand corporations’ efforts to communicate their values and commitment to stakeholders after a crisis. Specifically, the study explores the characteristics of communication efforts that may differ depending on the reputational crisis types: corporate ability (CA) and corporate social responsibility (CSR) crises. Employing a series of semantic network analyses, the study examined the sustainability annual reports of two Korean airlines (i.e., Korean Air and Asiana Airlines) published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Anwar (2015) analysed the communication patterns in the annual reports of corporates during global financial crisis times of 2008 and found that they were distinctive in the pre- and post-crisis periods. Similar studies have been conducted on corporate and CSR communications in company annual-, sustainability- and management- reports during a crisis (D’Aveni and MacMillan, 1990; Dias et al , 2016; García-Benau et al , 2013; Gastone, 2020; Hatani, 2019; Khanna and Irvine, 2012; Park et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 60%
“…Anwar (2015) analysed the communication patterns in the annual reports of corporates during global financial crisis times of 2008 and found that they were distinctive in the pre- and post-crisis periods. Similar studies have been conducted on corporate and CSR communications in company annual-, sustainability- and management- reports during a crisis (D’Aveni and MacMillan, 1990; Dias et al , 2016; García-Benau et al , 2013; Gastone, 2020; Hatani, 2019; Khanna and Irvine, 2012; Park et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 60%
“…In this study, we first conducted a semantic network analysis. A semantic network refers to the way words are semantically related to each other (Doerfel & Barnett, 1999;Park, Kim, & Rim, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we first conducted a semantic network analysis. A semantic network refers to the way words are semantically related to each other (Doerfel & Barnett, 1999; Park, Kim, & Rim, 2020). Semantic network analysis employs network analytical methods based on shared meaning in paired associations (Abu‐Salih, Wongthongtham, Chan, & Zhu, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The next study, “Exploring Variations in Corporations’ Communication After a CA Versus CSR Crisis: A Semantic Network Analysis of Sustainability Reports” by Park et al (2020), also explores CSR communication values in a novel comparison framework. Specifically, the authors investigate convergence and divergence for promoting shared values in sustainability reports following a crisis in corporate ability (CA)—the actual performance of operations—versus a CSR crisis involving social responsibility.…”
Section: Overview Of Csr Articlesmentioning
confidence: 99%